BORDER GUARDS’ FOREIGN LANGUAGE TRAINING IN THE EUROPEAN UNION COUNTRIES AND UKRAINE: COMPARATIVE STUDY (Comparative Professional Pedagogy, 2021)
The article reveals the results of the comparative study of the foreign language training of border guards in the European Union countries and Ukraine. It has been established that the Basic training program at the Main Training Center of the Personnel of the State Border Guard Service of Ukraine is to a great extent harmonized with the Common Core Curriculum for basic training of European border guards and is in line with the Sectoral Qualifications Framework for border guarding in European Union countries. A comparative analysis of compliance of foreign language training subjects in the system of training of personnel of the European Union border guard agencies revealed certain professionally-oriented topics, that are missing from the Ukrainian basic training program for border guards. Absence of the mentioned subjects can be explained by their peculiar features characteristic for European Union border guard’ functions, including different border guard services structure, key European border security related documents. Some of the absent subjects are partially covered in the Ukrainian training program, such as “Cross-border crime” which envisages types of crimes, criminals, smuggled goods, weapons and is studied within the topic “Border checks”, the subject “Apprehension, detention and return” is partially covered in the topics “Conflict resolution” and “Border checks”. Also, there are subjects almost completely absent from the national training program, such as: “Fundamental rights”, “Providing first-aid”, “Public service”, although the national training program includes basic principles, case studies and role-plays on these subjects. Thus, the prospects for further scientific research encompass studying the possibility of practical implementation of the European experience of border guards’ foreign language training into the system of personnel professional training of the State Border Guard Service of Ukraine.
Keywords: professional foreign language training; border guards; common educational standards; European Union countries